Underwater arbitrary distance measurement using laser frequency comb with simultaneous correction of underwater refractive index. (30th November 2022) - Zhao, Haihan; Xu, Xinyang; Li, Wei; Shi, Haonan; Qian, Zhiwen; Sun, Wanzhong; Zhai, Jingsheng
Highlights: Utilizing dispersive interference and spatial light folding optical path to perform the measurement of arbitrary distance underwater. Measure the group refractive index of water simultaneously and complete the correction of refractive index. Complete high-precision underwater arbitrary distance measurement. The experimental uncertainty is better than 18.5 μm in the detection range of 8 m underwater. Abstract: With the development of marine science and technology, underwater ranging has been widely applied in underwater remote sensing, detection, and navigation. In this paper, we propose a method aimed at obtaining arbitrary distance underwater using frequency comb, i.e., measuring arbitrary positioned points by using spectral interference and spatial folding optical paths. Moreover, the simultaneous correction of the water refractive index is implemented in the measurement scheme. The compensation of the refractive index also perfects the measuring mechanism to some extent. The experimental results show that the difference is well within 18.5 μm compared to the reference value over a range of 8 m, and the Allan deviation is 0.96 μm at 100 s averaging time.